2015
DOI: 10.1073/pnas.1419799112
|View full text |Cite
|
Sign up to set email alerts
|

Sparse feature selection methods identify unexpected global cellular response to strontium-containing materials

Abstract: Despite the increasing sophistication of biomaterials design and functional characterization studies, little is known regarding cells' global response to biomaterials. Here, we combined nontargeted holistic biological and physical science techniques to evaluate how simple strontium ion incorporation within the well-described biomaterial 45S5 bioactive glass (BG) influences the global response of human mesenchymal stem cells. Our objective analyses of whole gene-expression profiles, confirmed by standard molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 55 publications
3
58
0
Order By: Relevance
“…Furthermore, strontium ions are known to enhance osteoblastic bone formation and reduce osteoclastic bone resorption (Marie et al, 2001), and they are used for the treatment of osteoporosis (Marie, 2005). Strontium-containing bioactive glasses (BG) have been shown to release strontium ions when in contact with aqueous solutions (Fredholm et al, 2012), and they have been suggested to combine the benefits of strontium ions with those of BG (bioactivity, apatite formation, controlled release of therapeutic ions, and delivery versatility) (Gentleman et al, 2010;Autefage et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, strontium ions are known to enhance osteoblastic bone formation and reduce osteoclastic bone resorption (Marie et al, 2001), and they are used for the treatment of osteoporosis (Marie, 2005). Strontium-containing bioactive glasses (BG) have been shown to release strontium ions when in contact with aqueous solutions (Fredholm et al, 2012), and they have been suggested to combine the benefits of strontium ions with those of BG (bioactivity, apatite formation, controlled release of therapeutic ions, and delivery versatility) (Gentleman et al, 2010;Autefage et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…9 These machine-learning methods have been successfully applied to QSAR modeling of diverse data sets. 1,2,5,[15][16][17][18][19][20][21][22] They can be further improved by using a sparsity-inducing Laplacian prior ∑ ห‫ݓ‬ ห ே ೢ ୀଵ (denoted as Bayesian regularized artificial neural networks with a Laplacian prior, BRANNLP) 8,9 which enables the irrelevant weights in feature space to be set to zero, leaving the remainder to define the model. In practical terms this means that both the less relevant descriptors and the number of effective weights in the neural network model are pruned to the optimal level.…”
Section: Machine Learning Methods Employing Em Learning and Sparse Prmentioning
confidence: 99%
“…Nano-analytical electron microscopy is also being applied to gain insights into cardiovascular tissue calcification (Bertazzo et al, 2013;Autefage et al, 2015), while porous silicon nanoneedles have been devised for sensing intracellular pH changes and enzyme activities, and for delivering drugs, nanoparticles and nucleic acids (Chiappini et al, 2015a,b).…”
Section: Materials Science and Tissue Engineering Approaches To Cardimentioning
confidence: 99%